Awakened - Murray, James S. (James Stephen), 1976-; Wearmouth, Darren (HarperCollins, 2018)
After years of waiting, New York's newest subway line is finally ready. Many dignitaries, including the American President, are in attendance for the inaugural run. When the train pulls into the station, they see that all the train cars are empty and the cars' interiors are drenched in blood. As chaos descends, all those in the pavilion scramble to get out. But the horror is only beginning. There's something living beneath New York City, and it's not happy we've woken it up.